Relationship between Mindfulness, Emotional Regulation and Teaching Efficacy in School Teachers - Agrawal, Chinu; Kumar, Rakesh; Jain, Aashi (JOURNAL OF INDIAN EDUCATION, 2023)
The presence of mind while teaching as well as the management of their emotions is a crucial part of teachers’ sense of efficacy in the classroom. This study aims to find the relationship between mindfulness, self-efficacy and emotional regulation in school teachers. A sample of 110 school teachers who were proficient in English was taken. They were given a self-reported questionnaire containing demographic information, the Five Facet Mindfulness Questionnaire (FFMQ) to measure mindfulness, the Teachers’ Sense of Efficacy Scale (short form) to measure the perceived efficacy of teachers in the classroom and the Emotion Regulation Questionnaire (ERQ) to measure their emotional regulation. It was found that mindfulness and emotional regulation were significantly and positively correlated with teachers’ sense of efficacy. Hence, results suggest that being more mindful and having a higher ability to regulate and manage emotions can lead to higher teaching effectiveness and efficiency in the classroom. These results contribute to the growing literature about awareness related to school teachers’ effectiveness in the classroom and will help in establishing innovative programmes and designing further research in future.